CHRISTIAN FUNERAL RITES AND RAMBU SOLO’ IN TANA TORAJA - Maulana, Abdullah Muslich Rizal; Karomi, Kholid; Ahyadi, Nur Afifah R Arman (Harmoni, 2023)
This article aimed to elaborate on the death ritual carried out by the society of Tana Toraja. Tana Toraja people, apart from their official affiliation to Christianity, yet practised an indigenous ceremony known as Rambu Solo’ as a part of Aluk Todolo, which is identified as a local belief system of the Tana Toraja. To describe a proper image of both rituals simultaneously, this paper used some methods: structuralism, comparison, and interviewing. The structuralism method of research came more profound into a comprehension of the funerals regarding their prominent position within Tana Toraja people; the comparison method traced both similarities and differences of the ritual based on its theological origin and practises while interviewing was done formulating pieces of information derived from Tana Toraja religious figures and intellectuals, stood for an additional effort enriching available documented sources. This research concluded that the community of Tana Toraja combined their death ritual from both Christianity and Rambu Solo’ basis, making it an inevitably distinguished ritual practise. Considering the traditions’ divergent values, the discussion suggests multiple identity belongings in the local Indonesian context.